Bandwidth Management for Intranets Using Multicast Firewalls - Tat, Chee Wan; Chee, Hoong Leong; Chee, Ronnie Weng Thum (Universiti Putra Malaysia Press, 2000)
Multimedia applications utilizing multicast transmission techniques are becoming prevalent as the number of users and types of applications proliferate. Nonetheless, the deployment of such applications throughout an Intranet is constrained by the lack of multicast capable routers and the inability to protect the network from being swamped by multicast traffic